HUBUNGAN ANTARA STRESS MENGERJAKAN TUGAS AKHIR DENGAN POLA MENSTRUASI PADA MAHASISWA KELAS 3A D3 KEBIDANAN STIKES BINA SEHAT PPNIÂ Â MOJOKERTO - Mardiyana, Rina; Ratna Ulandari, Eva (JURNAL KEPERAWATAN BINA SEHAT, 2014)
Menstrual is natural proccess due to women. Most of women due to some changes of menstrual pattern during reproduction period. In influencing to menstrual pattern, neuroendocrinology system has big role in women reproduction when they’re stress. This study aimed to determine the relationship between stress in doing final duty and menstrual pattern of midwifery undergraduates in Stikes Bina Sehat PPNI Mojokerto.This study uses correlation analytic design with cross sectional approach. The pojpulation is all class A midwifery undergraduates that doing final duty in Stikes Bina Sehat PPNI Mojokerto as many as39 people. The sampling technique used is total sampling. Independent variable is stress, and dependent variable is menstrual pattern. The results suggests that all of respondents (100%) that due to very severe stress is being polimenorrhea, all of respondents (100%) that due to severe stress is being normal menstrual, most of respondents (52.4%) that due to moderate stress is being normal menstrual, almost all of respondents (84.6%) that due to mild stress is being normal menstrualand all of respondents (100%) that do not due to stress is being normal menstrual. Getting severer stress level, due to menstrual disturbance to of midwifery undergraduates in Stikes Bina Sehat PPNI Mojokerto. Stress activate amygdale in lymbic system. This system will stimulate hipothalamic hormone releasing. That hormone direct or undirectly cause GnRH level decreasing, where passing this way, stress cause menstrual cycle.Keywords:stress, menstrual pattern, undergraduates, final duty